A Comparison of Hemoglobin Measured by Co-Oximetry and Central Laboratory During Major Spine Fusion Surgery. Issue 3 (June 2016) - Carabini, Louanne M.; Navarre, William J.; Ault, Michael L.; Bebawy, John F.; Gupta, Dhanesh K.
Abstract : (Abstracted from Anesth Analg, 120:60–65, 2015) Morbidity associated with packed red blood cell (PRBC) transfusion has led both the American Society of Anesthesiologists and the American Association of Blood Banks to advocate a restrictive approach to transfusion. Accurate and rapid measurement of hemoglobin (Hgb) concentration during surgery is vital in the effort to limit exposure to inadequate oxygen delivery while minimizing the exposure to excessive red blood cell transfusion.